Tolosa-Hunt syndrome and recurrent painful ophthalmoplegic neuropathy, case reports: what to do and when? - Daniele Frattini; Alessandro Iodice; Carlotta Spagnoli; Susanna Rizzi; Carlo Alberto Cesaroni; Michela Cappella; Carlo Fusco (Italian Journal of Pediatrics, 2023)
Abstract Background Tolosa-Hunt syndrome (THS) and recurrent painful ophthalmoplegic neuropathy (RPON) are rare diseases reported within the “Painful lesions of the cranial nerves” section of the International Classification of Headache Disorders-3rd edition (ICHD-3). In case of a first painful attack, differential diagnosis could be challenging and many pitfalls are due to the rarity of the disorders and the lack of information about correct medical management in youngsters. Case presentation Our main purpose was to report a new case of THS and a new case of RPON describing management and diagnostic investigation at the time of the first episode. In both cases of THS (13 years old) and RPON (14 years old) a unilateral periorbital headache associated with acute onset of ipsilateral third cranial nerve paresis, scarcely responding to non-steroidal anti-inflammatory drugs (NSAID), was present at the beginning of the first attack. Brain MRI with "time-of-flight" (TOF) angiography and the need to administer steroids (after 72 h from onset) in order to stop pain were the most important handles allowing us to adopt the correct management both in THS or RPON since onset and to face recurrences in RPON by avoiding useless therapy during follow-up. Conclusion Unilateral periorbital headache associated with third-fourth or sixth cranial nerve paresis should ideally be investigated with a full work-up, comprehensive of brain MRI with TOF angiography since the first attack. In cases with negative brain MRI spontaneous resolution should be considered and watchful waiting might be advisable before starting steroid therapy.